2022
DOI: 10.1039/d1gc04556c
|View full text |Cite
|
Sign up to set email alerts
|

NHC–palladium-catalyzed ionic liquid-accelerated regioselective oxyarylation of alkynes with diaryl ethers

Abstract: The first NHC-palladium-catalyzed regioselective oxyarylation of oxime ether in task-specific ionic liquid via C(sp3)-O and C(sp2)-O bond cleavage of two different type ethers for the assembly of structurally diverse 4-arylisoxazoles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In 2022, Li et al reported an elegant C(sp 3 )–O and C(sp 2 )–O bond cleavage strategy for the construction of structurally diverse 4-arylisoxazoles via NHC-palladium-catalyzed oxyarylation of oxime ether and diaryl ethers in ionic liquid in very good yields (up to 57–91%) with a broad range of functional groups tolerance (Scheme ). Remarkably, this chemical transformation represents the first regioselective cleavage and cross-coupling reaction of two different types of C–O bonds with diaryl ethers as the aryl source. It is worth noting that this catalytic system could be reused up to eight times without significant loss of catalytic activity.…”
Section: Synthesis Of Heterocycles With Two Different Heteroatomsmentioning
confidence: 99%
“…In 2022, Li et al reported an elegant C(sp 3 )–O and C(sp 2 )–O bond cleavage strategy for the construction of structurally diverse 4-arylisoxazoles via NHC-palladium-catalyzed oxyarylation of oxime ether and diaryl ethers in ionic liquid in very good yields (up to 57–91%) with a broad range of functional groups tolerance (Scheme ). Remarkably, this chemical transformation represents the first regioselective cleavage and cross-coupling reaction of two different types of C–O bonds with diaryl ethers as the aryl source. It is worth noting that this catalytic system could be reused up to eight times without significant loss of catalytic activity.…”
Section: Synthesis Of Heterocycles With Two Different Heteroatomsmentioning
confidence: 99%
“…The reactions take place via regioselective oxyarylation of oxime ethers 140 followed by IL-mediated cleavage of the C(sp 3 )–O and C(sp 2 )–O bonds in 140 and 141 (Scheme 46 ). 107 Firstly, the IL plays a key role as a source of bromine, which is likely to be involved in the oxyarylation step, and secondly, it serves as a green catalyst, implying that it promotes the desired chemical reactions with high efficiency while minimizing environmental impact. Additionally, the IL provides the necessary conditions for hydrogen bonding and alkaline conditions, and it can be recycled and reused eight times without any significant loss of effectiveness.…”
Section: Construction Of Heterocycles Catalyzed By Ionic Liquidsmentioning
confidence: 99%
“…reported the palladium‐catalyzed carbonylative Suzuki cross coupling reactions using AFA [8e] and NFSac [8f] respectively as CO surrogates. A catalyst for the carbonylative Suzuki cross coupling reaction, N ‐Heterocylic Carbene‐Palladium (NHC−Pd) [8g–i] complex, was reported by Zheng et. al .…”
Section: Introductionmentioning
confidence: 99%